Accelerating Africa's food production in response to rising food prices: Impacts and requisite actions - Diao, Xinshen; Fan, Shenggen; Headey, Derek D.; Johnson, Michael E.; Nin-Pratt, Alejandro; Yu, Bingxin (International Food Policy Research Institute, 2008)
In Africa the global food crisis threatens the livelihoods of millions of people who because of high rates of poverty, hunger, malnutrition, and food dependency are already exceptionally vulnerable. In better circumstances, Africa's agricultural sector would respond to rising prices by increasing food supply. But such a response is impossible without significant new policy actions on both the production and marketing of African agriculture. This paper assesses the likely impacts of two strategic policy options: doubling African staples production, and improving "market access" through regional integration and lowering transaction costs. Using an economywide multimarket model for 17 African economies and econometrically estimated parameters describing the relationships between growth and poverty and between public spending and growth, we assess the impacts of these two strategic options on Africa's food markets and its broader economic development. Doubling staples production significantly increases food security, reduces consumer food prices by roughly 25 percent, reduces producer prices by 10 percent (thus raising farm revenue), accelerates agricultural growth rates, facilitates broader economic growth through new agroprocessing and export opportunities, and lifts more than 100 million Africans out of poverty. Key policy actions are needed to move from this strategic vision to implementation. The first set of actions requires investing $38 billion from 2009 to 2013, or $7.5 billion per year, in a well-designed package of modern agricultural inputs and provisions. The second requires improving and extending transport infrastructure, especially major transport corridors and rural feeder roads. The third requires reducing tra*de barriers, which still remain much higher in agriculture than in other sectors. All of these actions are technically and financially feasible, but their timely implementation requires urgent initiatives by both national and international policymakers.--Authors' Abstract